Impact of distinct levels swimming crab shell powder (Portunus pelagicus) supplementation on in vitro rumen fermentation properties processed with phosphoric acid as a chitosan source. Issue 1 (1st June 2022) - Anggraeni, A S; Sofyan, A; Jayanegara, A; Laconi, E B; Kumalasari, N R; Herdian, H; Darma, I N G
Abstract: The major goal of this study was to see how adding swimming crab shell to dietary feed affected in vitro gas production and fermentation of feed in ruminal fluid Completely Randomized Design (CRD) with five treatments and four replications was arranged on this research. The treatments are RJ0 as control negative (0% of SCS supplementation of DM), RJ1(10% SCS), RJ2 (20% SCS supplementation), RJ3 (30% SCS supplementation), and RJ4 as possitive control (1% commercial chitosan supplementation). The highest gas production given by RJ0 treatment than other treatment. Total gas production 1-48 hours, rate of gas production (c), microbial cell protein, IVDMD, IVOMD of supplementation of SCS was significantly affected by treatments (P<0.05). Gas production from total fraction ( a+b ), soluble fraction ( a ) and insoluble fraction (b), NH3 production, and ammount of protozoa indicated no significant difference (P>0.05) among treatments. In this study basal diets supplemented with 30% SCS treatment had the best result as chitosan source on rumen fermentation properties in vitro.